Unveiling Oral Anaerobic Bacteria Outer Membrane Vesicles: A Comprehensive Systematic Review - Castro-Vargas, Priscilla; Barloy-Hubler, Frédérique; Acuña-Amador, Luis (Odovtos - International Journal of Dental Sciences, 2024)
Extracellular vesicles (EV) are spherical structures limited by membranes and shed by several cell types. Specifically, outer membrane vesicles (OMVs) are nanometric particles constitutively produced by Gram-negative bacteria (GNB) under different environmental conditions. OMVs are biologically active; they are loaded with selected lipids, polysaccharides, proteins, and even different types of nucleic acids. OMVs from pathogenic oral bacteria play key roles in pathogen-host interactions, constituting a possible link between oral health and systemic disease. OMVs participate in adhesion, invasion, and damage to cells, as well as in modulating the host's immune response, biofilm formation, and promotion of virulence. The objective of this systematic review was to collect, analyze and synthesize the knowledge available on literature reviews on OMVs of the most studied pathogenic oral anaerobic GNB. This information was classified into the following categories: induction of vesiculation and biogenesis, its liberation from the parental cell, content, internalization by another host cell, and the interaction with the host cell. It was found that the most studied OMVs are those of Porphyromonas gingivalis and Bacteroides spp. and, to a lesser extent, Aggregatibacter spp., and Treponema spp. This systematic review provides a synthesis of the current knowledge regarding OMVs, with emphasis on the information available for periodontopathogens.